PENERAPAN MODEL PEMBELAJARAN COLLABORATIVE LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PRAKTEK SANGGUL DAERAH - Rohmawati, Helmia Cipta; Kuswati, Teti (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2024)
This research aims to improve learning outcomes in the Basic Hair Styling course (regional bun) for students of the Aks-Akk Yogyakarta cosmetology study program for the 2023/2024 academic year using the Collaborative Learning learning model, so that it can foster the character of students who are able to think critically, actively, creatively, independently and innovatively. This study has a subject, namely 38 students of the Cosmetology Study Program who took the Basic Hair Styling course (regional bun). This research method uses the classroom action research method (PTK) with the Suharsini Arikunto model approach. The data collection technique used uses non-test techniques where the assessment is based on the results of student practice in cycle I, , then in the second cycle the assessment is not only the total look of the practice results but also consists of the results of presentation/demonstration, responsibility, cooperation and completeness of the paper. The results of the study show that there is a percentage of success of students of the cosmetology study program in the Basic Hair Styling course (regional bun) with learning Collaborative Learning, an increase in learning outcomes of 42.1% for A grades in the second cycle from 44.7% to 86.8.9%. Thus, collaborative learning can improve learning outcomes by emphasizing student cooperation and responsibility in learning and understanding lecture materials that are able to provide stimulation for students to be more active, creative and independent.